2015
DOI: 10.1386/jfs.3.1.7_1
|View full text |Cite
|
Sign up to set email alerts
|

From Holy Land to ‘Hallyu Land’: The symbolic journey following the Korean Wave in Israel

Abstract: The majority of academic literature on Hallyu, or the Korean Wave, focuses on its acceptance in the geographically and culturally proximate societies in Asia and the economically wealthy markets of North America. Very little attention has been given to other regions such as Africa, South America and the Middle East. Thus, looking at the Israeli case study allows us to examine how Korean culture is being accepted in non-Asian, non-western and non-English contexts. The most salient characteristic of Hallyu fans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…As Gellner (2006, p. 7) points out, banal nationalism can be formed when “two men are of the same nation if and only if they recognize each other as belonging in the same nation.” In the BTS sphere, there are also frequent remarks on belonging to online communities similar to belonging to a physical home-like space or a nation-state. The sense of togetherness is one of the most significant fundamentals of BTS communities, but not a physical nation-state (Lyan & Levkowitz, 2015). As Schneider (2018, p. 236) points out, “the need for community cohesion that nationalism relies upon indeed connects seamlessly with the kind of group dynamics that many digital technologies today promote,” and BTS fans utilize digital media to build their solidarity.…”
Section: Cyber-nationalism In a Bts Nation: Army As Bulletproof For Btsmentioning
confidence: 99%
“…As Gellner (2006, p. 7) points out, banal nationalism can be formed when “two men are of the same nation if and only if they recognize each other as belonging in the same nation.” In the BTS sphere, there are also frequent remarks on belonging to online communities similar to belonging to a physical home-like space or a nation-state. The sense of togetherness is one of the most significant fundamentals of BTS communities, but not a physical nation-state (Lyan & Levkowitz, 2015). As Schneider (2018, p. 236) points out, “the need for community cohesion that nationalism relies upon indeed connects seamlessly with the kind of group dynamics that many digital technologies today promote,” and BTS fans utilize digital media to build their solidarity.…”
Section: Cyber-nationalism In a Bts Nation: Army As Bulletproof For Btsmentioning
confidence: 99%
“…Aside from the fact that K-dramas were sold more cheaply than Japanese ones, many scholars found that the popularity of K-drama revealed a female-led consumption due to a strong focus on romance (Shin, 2007;Siriyuvasak & Hyunjoon, 2007;Jung, 2011;Jiang & Leung, 2012;Ainslie, 2015;Lyan & Levkowitz, 2015). Like other scholars, Otmazgin and Lyan (2014), in their study of Israeli fans, observed that most female fans were in their late teens or early twenties when the drama My Lovely Kim Sam Soon, broadcast in Israel in 2006, ignited the wave there.…”
Section: Hallyu 10 As a Transnational Popular Culturementioning
confidence: 99%
“…Aside from the fact that K-dramas were sold more cheaply than Japanese ones, many scholars found that the popularity of K-drama revealed a female-led consumption due to a strong focus on romance (Shin, 2007;Siriyuvasak & Hyunjoon, 2007;Jung, 2011;Jiang & Leung, 2012;Ainslie, 2015;Lyan & Levkowitz, 2015). Like other scholars, Otmazgin and Lyan (2014), in their study of Israeli fans, observed that most female fans were in their late teens or early twenties when the drama My Lovely Kim Sam Soon, broadcast in Israel in 2006, ignited the wave there.…”
Section: Confucianism and The Yonsama Syndrome In The Narrative Of K-...mentioning
confidence: 99%